A Systematic Literature Review: Parasocial Interaction in Adolescents - Qaulan Sadida; Suryanto Suryanto (Penerbit Lafadz Jaya, 2022)
Parasocial interaction is an illusion of intimacy with idol figures or media characters. This literature review aims to examine the phenomenon of parasocial interaction and its relation to adolescents; how the characteristics of the participants in the article, the measuring tools used, and the determinant factors. The research method used is a systematic literature review. Article searches were conducted online with the keywords “parasocial interactions” and/or “adolescents”. A total of 20 articles during the period 2013-2022 were used from Scopus, Proquest Dissertation, Sage Journals and ScienceDirect. The results of this literature review show that the research participants are teenagers, both boys and girls in various countries. The measuring instrument in the quantitative approach uses a parasocial interaction questionnaire that has been tested by previous research and has been modified according to the research context. In the qualitative approach, the methods chosen were interviews and focus group discussions. Parasocial interaction is one way for adolescents to form their self-identity and relationship expectations in the real world. Factors that influence parasocial interactions in adolescents include age, gender, media exposure, and character stereotypes. The results of this literature review can serve as a reference for other researchers who are interested in investigating parasocial interactions and their impact on adolescents.